Why Tobacco Farmers Still Standing ? (Case Study In Genteng Village, Sukasari District, Sumedang Regency) - Muhammad Edi Irfandianto; Dika Supyandi (HABITAT, 2020)
Tobacco, is one of the important commodities in Indonesian agriculture. The main tobacco products are tobacco leaves and cigarettes. The demand for tobacco products is estimated to continue to increase every year, giving high income to Indonesia. Sumedang Regency is identical to tobacco, one of which is in Sukasari District, there is a village that has potential for tobacco commodities, namely Genteng Village. The majority of its citizens work as tobacco farmers. The purpose of this study was to obtain a history of the development of tobacco farming in Genteng Village, Sukasari District, Sumedang Regency and also obtain a description of why tobacco farmers still continue to do tobacco farming in Genteng Village, Sukasari District, Sumedang Regency. The design in this study uses a qualitative design with case study research techniques. Data collection methods in this study used in-depth interview, observation and literature studies. Respondents and informants in this study were chosen purposive with certain considerations. Data analysis uses interactive analysis model and fishbone diagram. The results of this study indicate that based on the history of tobacco development in the Genteng Village, tobacco farming in the Genteng Village, Sukasari District, Sumedang District has continued to run since village was founded in 1845 There are 5 categories of causes that tobacco farmers continue to do tobacco farming, that is survival, parents' encouragement, young age, education level and land availability. Survival is the main category.